If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3z + 10 = -2z + 6 Reorder the terms: 10 + 3z = -2z + 6 Reorder the terms: 10 + 3z = 6 + -2z Solving 10 + 3z = 6 + -2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '2z' to each side of the equation. 10 + 3z + 2z = 6 + -2z + 2z Combine like terms: 3z + 2z = 5z 10 + 5z = 6 + -2z + 2z Combine like terms: -2z + 2z = 0 10 + 5z = 6 + 0 10 + 5z = 6 Add '-10' to each side of the equation. 10 + -10 + 5z = 6 + -10 Combine like terms: 10 + -10 = 0 0 + 5z = 6 + -10 5z = 6 + -10 Combine like terms: 6 + -10 = -4 5z = -4 Divide each side by '5'. z = -0.8 Simplifying z = -0.8
| logx(3x^2-4x-6)=2 | | 2x+14=7x-6 | | m^2-4m=10 | | 3y-2=18-y | | -x-19=15-3x | | (4x+1)(x-5)= | | .4x+13.5*.6=10 | | 4x^3y^2+8xy-12x^3y=0 | | 121-6x=-55+5x | | 3x-9+2x-3=6x+12-8 | | x(4+5)=5(x-2) | | 3(x+1)+6=-12 | | 121-6x=-55+5 | | 12-2m+5=-5 | | ax+7y=8 | | 3(x+0.1)-4(x-0.5)=5.4 | | -2y-5=y+4 | | 3d-11-7d=5 | | 3(x+0.1)-4(x-0.5)=54 | | 5(m-2)=8(m-2) | | log[2](3x+6)=4 | | 5x(x+5)=0 | | y=(x^2-5)(x^2-x^3) | | x=7i | | 152=-3+5(1+6n) | | -148=3(4+4x)+8x | | (4x+2)-(3x-3)=8 | | -11=x-18 | | (17/30)/(3)=z | | (17/30)/(1/3)=z | | 0=-16t^2+128-256 | | 0=-16t^2+128t-192 |